Effects of Flow on Scales Formation in a CO2 Saturated Brine Environment. (5th January 2017) - Hassan SK, Mobbassar; Abdullah, Aboubakr Moustafa; Ko, M; Laycock, Nicholas; Ingham, Bridget; Williams, David E
Abstract : A significant amount of literature exists demonstrating the effect of CO2 on corrosion scale formation under non-flow conditions. However, literature available on the effects of flow on the nature and protectivity of corrosion scale has many contradictions. This work demonstrates the effects of flow on the nature of corrosion scale for five different oil-field grade steels of varying chemistry (in terms of micro-alloying) and microstructures (ferritic /pearlitic and martensitic), in a CO2 saturated ( 1bar) brine (0.5 M NaCl) environment under three different pH (4.2, 6.3 and 6.8) conditions and different temperatures. Flow was introduced using a rotating disk electrode (RDE). The effect of flow was electrochemically characterized by chronoamperometry measurements at various temperatures and pH values. The morphology of the formed scale at the steel surface was analyzed by SEM. Similar to our previous findings, high pH (≥ 6.3) and high temperature ( 80 o C) found to favor the formation of protective crystalline scale. Within the preferred conditions (higher pH and temp.) of protective scale formation, higher flow rates in general caused the formation of a protective scale to be sluggish. At lower pH and temperatures, the non-protective scale showed their degree of non-protectivity by allowing higher current density passing through them. Higher Cr content in the steels led to higher degree of protectivity presumably by inducing a higher degree of supersaturation in the local environment which facilitated the formation of a protective crystalline scale. Also, higher Mo content appeared to make the formation of protective crystalline scale relatively sluggish.